Health TAPESTRY: Exploring the Potential of a Nursing Student Placement Within a Primary Care Intervention for Community-Dwelling Older Adults. (February 2020) - Valaitis, Ruta; Gaber, Jessica; Waters, Heather; Lamarche, Larkin; Oliver, Doug; Parascandalo, Fiona; Schofield, Ruth; Dolovich, Lisa
The increasing prevalence of chronic diseases in aging places demands on primary care. Nurses are the major nonphysician primary care workforce. Baccalaureate nursing programs should expose students to primary care and older adults to support these demands and help recruit new graduates to this setting. However, many baccalaureate nursing programs focus on acute care and placements aimed at older adults are viewed negatively. To address these curriculum challenges, third-year Canadian baccalaureate nursing students were placed in an innovative primary care program—Health TAPESTRY—for community-dwelling older adults. Health TAPESTRY involves an interprofessional primary care team, trained lay volunteers conducting home visits, system navigation, and an online software application. The goal of this study was to explore third-year baccalaureate nursing students' perceptions of this unique clinical primary care placement. This qualitative descriptive study explored students' perceptions of this placement's strengths, weaknesses, opportunities, threats (SWOT), and outcomes. Nursing students participated in focus groups ( n  = 14) or an interview ( n  = 1) and five completed narrative summaries following visits. Qualitative content analysis was supported by NVivo 10. Strengths of the clinical placement included training for the intervention; new insights about older adults; and experience with home visiting, interprofessional team functions, and community resources. Weaknesses included limited exposure to older adult clients, lack of role clarity, lack of registered nurse role models, and technology challenges. Opportunities included more exposure to primary care, interprofessional teams, and community resources. No threats were described. Nursing students' clinical experiences can be enhanced through engagement in innovative primary care programs. Adequate exposure to clients, including older adults; interprofessional teams; mentoring by registered nurses or advanced practice nurse preceptors; and role clarity for students in the primary care team should be considered in supporting baccalaureate nursing students in primary care clinical placements.